Relationship of Company Age and Industry Sector with FinancialPerformance –An Indian Evidence - Verma, Deepti Sehrawat; Sharma, Dr. Anand (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to analyze the relationship of the age of companies and the industry sector on financial performance variables for NIFTY 100 Index companies. The minimum age of a company in NIFTY 100 index was seven years and the maximum age is114 years. Further, these companies have been divided into nine industry sectors. To analyze the relationship, sixteen financial performance variables have been taken for the financial year 2019. It has been found that older companies have better performance in terms of return ratios, stakeholders-related ratios, leverage, replacement ratios. Younger companies have better operational efficiency and market valuation. It has also been observed that there is a significant difference in return ratios for Telecom and Utility, Financial, Industrial, Consumer staples, IT, Energy and Consumer Discretionary Sectors. The findings of this paper will enable investors in making prudent investment decisions and will enable them to understand how the age and industry of a company impact the financial performance of companies in India.